2015
DOI: 10.1016/j.limno.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Climate driven changes in the submerged macrophyte and phytoplankton community in a hard water lake

Abstract: a b s t r a c tWe studied the changes in the submerged aquatic vegetation (SAV) and phytoplankton community in a hard water lake during different meteorological conditions. We hypothesized that variations in climatic conditions (precipitation and temperature) can influence the physicochemical parameters of water and, in turn, affect SAV and phytoplankton development. The investigations were performed in Lake Rogóźno (the West Polesie region, Eastern Poland) over 10 years from 2003 to 2013. The physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…However, charophytes generally do not have higher light requirements than vascular plants. There are two alternative explanations for the decreased charophyte abundance: it has been suggested that the altered color of the water diminished the establishment of charophytes and provided an opportunity to competitors ( Ejankowski and Lenard, 2015 ). Middelboe and Markager (1997) suggested that the negative effect on charophyte growth can also be caused by the fact that colored substances reduce the pH of the water.…”
Section: The Effects Of Doc On Macrophytesmentioning
confidence: 99%
“…However, charophytes generally do not have higher light requirements than vascular plants. There are two alternative explanations for the decreased charophyte abundance: it has been suggested that the altered color of the water diminished the establishment of charophytes and provided an opportunity to competitors ( Ejankowski and Lenard, 2015 ). Middelboe and Markager (1997) suggested that the negative effect on charophyte growth can also be caused by the fact that colored substances reduce the pH of the water.…”
Section: The Effects Of Doc On Macrophytesmentioning
confidence: 99%
“…The acidification of water due to increasing CO 2 affects the growth and distribution of aquatic macrophytes (Short and Neckles, 1999). Seaweeds will benefit from the increase in inorganic carbon concentration as more CO 2 is available for their accessibility while growth of macroalgae will be reduced (Beardall et al, 1998;Kroeker et al, 2010;Ejankowski and Lenard, 2015). In nutshell, high CO 2 concentration promotes eutrophication which supports algal growth ultimately decreasing the light reaching the other plants hence decreasing their productivity.…”
Section: Co 2 Concentrationmentioning
confidence: 99%
“…Short ice cover duration on lakes can lead to intensive and long-lasting water mixing (Lenard and Wojciechowska, 2013), increases in nutrient concentrations, higher biomass of phytoplankton and lower biomass of zooplankton, and much higher water turbidity (Weyhenmeyer et al, 2008;Laugaste et al, 2010). Hence, mild winters can negatively affect the underwater light climate, which modifies conditions for the development of submerged aquatic vegetation in lakes (Ejankowski and Lenard, 2015). Nevertheless, in Charadominated lakes, the extensive overwintering charophytes can hamper the development of phytoplankton species by modifying their responses to nutrient concentrations, thus weakening the unfavourable effects of a mild winter on water quality (Pełechata et al, 2015).…”
Section: Introductionmentioning
confidence: 99%